Zone Landslide Analysis Using Geophysical Method and Analysis of Soil Type for Disaster Mitigation In Waru Pamekasan - Sandy Vikki Ariyanto; Idon Joni (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2019)
The results of this study are the factors of landslides there are many cracks in the ground, normal faults, shear faults and slope of the soil surface. The higher the slope of the land surface, the more potential for landslides. Results of XRF Waru 1 Si 58.3%, Waru 2 Ca 71.37%, Waru 3 Si 43.3%. The results of XRD Waru 1 and Waru 2 were 88% SiO2 compound, Waru 3 in the form of CaCo3 compound was 75.2%. SEM results with 10,000x enlargement Waru 1 is almost homogeneous in the form of slabs which identifies an uneven grain size and with a little porosity indicating the sample is partially amorphous in structure, Waru 2 shows an inhomogeneous sample with a fairly high porous dispersion and is not equally, Waru 3 shows the existence of an almost cube crystal form with high porosity so that it causes frequent landslides due to the density of a sand is still lacking so that it makes it easy for the land to be evicted because there are still many cavities in the soil.